Successful Bone Marrow Transplantation in a Patient with Acute Myeloid Leukemia Developed from Severe Congenital Neutropenia Using Modified Chemotherapy and Conditioning Regimen for Leukemia - Risa Matsumura; Shinji Mochizuki; Yusuke Morishita; Hiroko Hayakawa; Shuhei Karakawa; Hiroshi Kawaguchi; Satoshi Okada; Nobuyuki Hyakuna; Masao Kobayashi (Hematology Reports, 2024)
Severe congenital neutropenia (SCN) is characterized by chronic neutropenia with recurrent infections from early infancy and a predisposition to myelodysplastic syndrome/acute myeloid leukemia (AML). Allogeneic hematopoietic stem cell transplantation (HSCT) is the only curative treatment for patients with SCN who develop myelodysplastic syndrome/AML. We report an 8-year-old girl with SCN carrying an ELANE mutation that had been refractory to granulocyte colony-stimulating factor. The patient experienced recurrent infections and then developed AML. The counts of leukemic blasts that harbored both CSF3R and RUNX1 mutations spontaneously decreased with antimicrobial therapy, leading to partial remission. After AML recurrence, HSCT was successfully performed using modified chemotherapy and a conditioning regimen. Serial donor lymphocyte infusions against mixed chimerism induced complete donor chimerism over 4 years without any infections or AML relapse. This case suggests the importance of carefully managing neutropenia-related infections, leukemia progression, and HSCT in patients with SCN developing AML.